THE ROLE OF THE GOVERNMENT IN ENTREPRENEURSHIP DEVELOPMENT: EVIDENCE FROM BOSNIA AND HERZEGOVINA - Zijad Džafić; Amra Babajić (Economic Review)
In recent decades, economic growth in countries around the world has become increasingly dependent on the dynamism of small and medium sized enterprises (SMEs). This is especially important in the transition economies. The creation of a new SME sector in Bosnia and Herzegovina (BiH) as a transition country may play an important role in the process of economic regeneration and job creation. The paper sets out an approach to analyzing the development of SMEs in BiH. We have focused on (i) attitudes of entrepreneurs in the private sector towards the role of government in SME development through provision of assistance to SMEs in BiH, (ii) the business environment in which firms operate, and (iii) attitudes of the employmed in government sector towards the role of government in SME development through the provision of assistance to SMEs in BiH. The paper reviews the literature on these three approaches and available evidence on relevance to understanding the performance of SMEs as main agents of entrepreneurship in the BiH.